Stiquito controlled! : - Conrad, James M. (Wiley, 2005)
Stiquito Controlled! is a widely accessible, user-friendly book that provides step-by-step instructions for building Stiquito, a small, multi-legged robot that resembles a "walking-stick" insect. The book includes comprehensive instructions and all the parts needed to complete assembly